Manajemen Peningkatan Kualitas Personalia di Lembaga Pendidikan Islam - Nurul Lailiyah (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2017)
Personnel management is management which gets at staffing issues in an institution. It needs smart and skilled employees to make them work effective and efficiently. Therefore, institution has to carry out strict selection in accepting new employees. Likewise, the institution aims will be reached if they have smart and skilled employees, and its amount is adequate. The main goal of personnel management is planning, procurement, development, promotion and transfer, dismissal, retirement, and welfare of employees. The rapid change in society should be followed schools by increasing its personal profession, and the capacity building is not based on their work experience only, since the length of profession practice is not an increasing ability guarantee. Thereof, the head master as manager can improve the personnel profession in various ways.